2020
DOI: 10.3390/su12229588
|View full text |Cite
|
Sign up to set email alerts
|

Food Provision, Social Interaction or Relaxation: Which Drivers Are Vital to Being a Member of Community Gardens in Czech Cities?

Abstract: Urban gardening provides city dwellers with a wide range of benefits. Research dealing with the benefits of community gardens (CG) is often qualitative, focused on their founders’ motivations. The objective of our contemporary quantitative study is to understand why the inhabitants of Czech cities join CGs. The paper answers the research question: “What drivers exist for members’ participation in CGs?” It also deals with how the drivers of CG members differ across CGs’ locations in different urban structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…These factors should be taken into account by urban planners and designers when implementing and retrofitting community gardens. The importance of such spatial factors is in contrast to the study on driving forces of residents engaging in Czech community gardens [30]. Dubová et al found that the location of the gardens within the urban pattern does not explain why people engage in community gardens.…”
Section: Implementing Urban Agriculturementioning
confidence: 94%
See 4 more Smart Citations
“…These factors should be taken into account by urban planners and designers when implementing and retrofitting community gardens. The importance of such spatial factors is in contrast to the study on driving forces of residents engaging in Czech community gardens [30]. Dubová et al found that the location of the gardens within the urban pattern does not explain why people engage in community gardens.…”
Section: Implementing Urban Agriculturementioning
confidence: 94%
“…The findings suggest that residents of Czech cities are motivated to engage in community gardens for recreational purposes, social exchange, and the joy of urban gardening. However, motives for joining community gardens can differ depending on previous gardening experiences, its lengths, and sociodemographic factors [30]. In a similar vein, the importance of the family tradition of commercial farming in Australia for pursuing sustainable livelihoods was confirmed by Diehl [34].…”
Section: Implementing Urban Agriculturementioning
confidence: 96%
See 3 more Smart Citations